STORIES OF SUFFERING AND GROWTH: AN INVESTIGATION OF THE LIVED EXPERIENCE OF NONATTACHMENT. Issue 2 (3rd July 2018) - Whitehead, Richard; Bates, Glen; Elphinstone, Bradley
ABSTRACT: The Buddhist concept of nonattachment refers to a flexible engagement with experience without fixation on achieving specified outcomes. The primary focus of this study was to qualitatively examine how nonattachment and attachment are experienced in individuals identified as having very high and low levels of nonattachment. Specifically, we examined individuals' descriptions of how their levels of nonattachment and attachment developed, and how nonattachment and attachment affect their lives, their relationships, and their understanding of personal development. Twenty-four in-depth interviews were conducted with participants (18 women, six men) aged 19 to 61 ( mean  = 36.20, standard deviation  = 11.00), drawn from a larger sample of 1191, who scored very high or very low on nonattachment. Thematic analysis revealed highly nonattached individuals were psychologically mature, and flexibly engaged with their experiences, allowing their life to flow with minimal self-obstruction. In contrast, highly attached individuals were quite fixed in their thinking and often placed unachievable expectations on themselves and others. Interestingly, transformative suffering was crucial in the development of nonattachment, whereas unresolved experiences of suffering contributed to the development of attachment.